2018
DOI: 10.1017/s0960258518000132
|View full text |Cite
|
Sign up to set email alerts
|

Three levels of simple morphophysiological dormancy in seeds ofIlex(Aquifoliaceae) species from Argentina

Abstract: As a contribution to understanding the world biogeography of seed dormancy in the cosmopolitan genus Ilex, we studied seeds of I. argentina, I. brasiliensis, I. brevicuspis, I. dumosa, I. paraguariensis and I. theezans from the subtropical region of Argentina. We hypothesized that seeds of these species have non-deep simple morphophysiological dormancy (MPD). Effects of temperature, cold stratification and gibberellic acid (GA3) on seed germination and embryo growth were tested. Regardless of incubation temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…Similar to our conclusion, Galíndez et al . (2018) have shown that seeds of Ilex argentina and I. paraguariensis have deep simple MPD. However, these authors also reported that seeds of several Ilex spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our conclusion, Galíndez et al . (2018) have shown that seeds of Ilex argentina and I. paraguariensis have deep simple MPD. However, these authors also reported that seeds of several Ilex spp.…”
Section: Discussionmentioning
confidence: 99%
“…Até o presente momento não se sabe ao certo o motivo da imaturidade do embrião e como pode ser contornada, sendo necessário um período de quatro e seis meses de estratificação para o amadurecimento do embrião (MIRESKI et al, 2019). Diferentes tipos de estratificação já foram testados, porém o tradicional, em que as sementes são acondicionadas entre duas camadas de areia úmida, é ainda o que apresenta maior eficiência, em comparação a estratificações a frio ou entre papel (GALÍNDEZ et al, 2018;SÁ et al, 2018;MIRESKI et al, 2019;SOUZA et al, 2019). Em síntese, verifica-se que as diversas modalidades de métodos adotados para vencer os impedimentos impostos à germinação de sementes das mais variadas espécies, encontradas sobretudo em florestas, são eficientes de acordo com as características peculiares de cada táxon.…”
Section: Metodologias Para Superação De Dormênciaunclassified
“…La multiplicación por semilla de la yerba mate presenta varias limitaciones tales como bajo porcentaje de germinación (13% a 14%), obteniéndose de esta manera, aproximadamente entre 20.000 a 22.000 plántulas/kg de semilla (Prat Kricun, 1993). El periodo requerido para el comienzo de la germinación es largo, entre 3 y 9 meses (Galíndez et al, 2018), hecho que demanda la siembra en almácigo, con los costos y superficie que esto implica (costo de oportunidad). A esto se debe sumar la necesidad de trasplante al contenedor final; mayor costo en mano de obra y largo período de viverización, de 12 a 15 meses.…”
Section: Grado De Relevanciaunclassified